Comparison of antimicrobial resistant genes in chicken gut microbiome grown on organic and conventional diet. (December 2016) - Hegde, Narasimha V.; Kariyawasam, Subhashinie; DebRoy, Chitrita
Abstract: Antibiotics are widely used in chicken production for therapeutic purposes, disease prevention and growth promotion, and this may select for drug resistant microorganisms known to spread to humans through consumption of contaminated food. Raising chickens on an organic feed regimen, without the use of antibiotics, is increasingly popular with the consumers. In order to determine the effects of diet regimen on antibiotic resistant genes in the gut microbiome, we analyzed the phylotypes and identified the antimicrobial resistant genes in chicken, grown under conventional and organic dietary regimens. Phylotypes were analyzed from DNA extracted from fecal samples from chickens grown under these dietary conditions. While gut microbiota of chicken raised in both conventional and organic diet exhibited the presence of DNA from members of Proteobacteria and Bacteroidetes, organic diet favored the growth of members of Fusobacteria . Antimicrobial resistance genes were identified from metagenomic libraries following cloning and sequencing of DNA fragments from fecal samples and selecting for the resistant clones ( n =340) on media containing different concentrations of eight antibiotics. The antimicrobial resistant genes exhibited diversity in their host distribution among the microbial population and expressed more in samples from chicken grown on a conventional diet at higher concentrations of certain antimicrobials than samples from chicken grown on organic diet. Further studies will elucidate if this phenomena is widespread and whether the antimicrobial resistance is indeed modulated by diet. This may potentially assist in defining strategies for intervention to reduce the prevalence and dissemination of antibiotic resistance genes in the production environment.